Novel Imidazole Substituted Bodipy-Based Organic Sensitizers in Dye-Sensitized Solar Cells - Mao Mao; Xiao-Lin Zhang; Guo-Hua Wu (International Journal of Photoenergy)
A comparative study on the photophysical, electrochemical properties and photovoltaic performances of pure imidazole dyes containing varying linker groups is done. Two new organic dyes containing 4,5-bis(4-methoxyphenyl)-1H-imidazole (BPI) unit as an electron donor, boron dipyrromethene (Bodipy) chromophore as a conjugate bridge, cyanoacetic acid as an electron acceptor, and phenylene (BPI-P) or thienyl (BPI-T) as a additional linker have been synthesized for fabricating dye-sensitized solar cells (DSSCs). A reference dye (DPI-T) with 6,9-dimethoxy-1H-phenanthro[9,10-d]imidazole as the donor has also been synthesized for comparison. The overall conversion efficiencies of 0.18%, 0.32%, and 1.28% were obtained for DSSCs based on BPI-P, BPI-T, and DPI-T, respectively. DPI-T was found to be more efficient than BPI-P and BPI-T because of its enhanced light harvesting efficiency and better coplanar geometry of the electronic structure.